Extracellularpolymeric substances' influence on membrane fouling and cleaning during microfiltration process - Nuengjamnong, C.; Cho, J.; Polprasert, C.; Ahn, K. -H. (PARTICLE SEPARATION 2005 - DRINKING WATER TREATMENT, 2006)
In this study, the influence of extracellular polymeric substances (EPS) on membrane fouling and cleaning efficiency was investigated during the microfiltration process, of a submerged membrane bioreactor (SMBR). Two lab-scale SMBRs with different solids retention time (SRT) were operated and the variation of bound (or extractable) EPS in the activated sludge floc was observed in terms of total organic carbon and protein concentration of the extracted EPS solution. Experimental results showed that as SIRT decreases, the amount of bound EPS in the activated sludge floc becomes higher. EPS had a positive influence on specific cake resistance to accelerate the membrane fouling. In order to clean the fouled membrane, de-ionized water flushing, chemical cleaning using sodium hypochlorite (NaOCI), and the combination of water flushing and chemical cleaning were performed. The flux recovery rate was calculated to quantify the cleaning efficiency and a microscopic image using scanning electron microscopy was taken to visualize the cleaning effect. It was found that the water flushing was not highly effective at removing the EPS formed in the cake layer. The chemical cleaning of membrane by 5,000 ppm NaOCI for 3 hours could be more effective to eliminate EPS.